Strain Gradient Programming in 3D Fibrous Hydrogels to Direct Graded Cell Alignment. Issue 1 (21st November 2022) - Kolel, Avraham; Ergaz, Bar; Goren, Shahar; Tchaicheeyan, Oren; Lesman, Ayelet
Abstract: Biological tissues experience various stretch gradients which act as mechanical signaling from the extracellular environment to cells. These mechanical stimuli are sensed by cells, triggering essential signaling cascades regulating cell migration, differentiation, and tissue remodeling. In most previous studies, a simple, uniform stretch to 2D elastic substrates has been applied to analyze the response of living cells. However, induction of nonuniform strains in controlled gradients, particularly in biomimetic 3D hydrogels, has proven challenging. In this study, 3D fibrin hydrogels of manipulated geometry are stretched by a silicone carrier to impose programmable strain gradients along different chosen axes. The resulting strain gradients are analyzed and compared to finite element simulations. Experimentally, the programmed strain gradients result in similar gradient patterns in fiber alignment within the gels. Additionally, temporal changes in the orientation of fibroblast cells embedded in the stretched fibrin gels correlate to the strain and fiber alignment gradients. The experimental and simulation data demonstrate the ability to custom‐design mechanical gradients in 3D biological hydrogels and to control cell alignment patterns. It provides a new technology for mechanobiology and tissue engineering studies. Abstract : Many biological tissues are under continuous stretch conditions, leading to the development of nonuniform tension, essential to tissue functionality. Here, a unique stretching platform is developed using designed geometries to generate programmed strain gradients along predetermined axes in 3D hydrogels. Cells embedded within the stretch‐induced gradient gels show remarkable patterns of alignment that gradually change throughout the 3D gel.